Solid‐State Nanochannels: Enzyme and AIEgens Modulated Solid‐State Nanochannels: In Situ and Noninvasive Monitoring of H2O2 Released from Living Cells (Small Methods 2/2020). Issue 2 (12th February 2020) - Lou, Xiaoding; Song, Yongjun; Liu, Rui; Cheng, Yong; Dai, Jun; Chen, Qing; Gao, Pengcheng; Zhao, Zujin; Xia, Fan
Abstract : In article number 1900432 by Fan Xia and co‐workers, living cells are first incubated on a flexible polyethylene terephthalate (PET) membrane and then inserted into the left chamber of a nanochannels device. When H2 O2 is released from living cells, a Tyr‐containing tetraphenylethylene (TPE) derivative (TT) forms horseradish peroxidase (HRP)‐modulated linkage in the nanochannels, which is covalently attached to capture probes. By using this dual‐signaloutput (ionic current and fluorescence) nanochannel device, in situ and noninvasive detection of H2 O2 can be achieved.